Analisis Status Ergonomi Posisi Kerja dan Kelelahan Kerja Pada Tenaga Kerja di CV. Sinar Albasia Utama Kalasan, Sleman, Provinsi D. I. Yogyakarta - Tyastiana Arbianisa; Agus Suwarni; Muryoto Muryoto (Poltekkes Kemenkes Yogyakarta, 2016)
Every year there are more than 250 million accidents in work places. Moreover, as many as 1.2 million workers die due to accidents and illness in their work places. Workers who do not do their work ergonomically can get a variety of effects, one of which is fatigue. The purpose of this study was to determine the relationship between ergonomic status of working position and the fatigue of workers in CV Sinar Albasia Utama, Kalasan, Sleman, Yogyakarta. The study was a survey with cross sectional design. The study population covers all workers in the production department of that industry who work in a standing position and using a work-base, i.e. 289 workers. The sampling selection used simple random sampling technique, and the data collect-ion instrument used was a questionnaire form of work-fatigue assessment. Based on the re-sults of cross tabulation relationship between ergonomic status of working position and work fa-tigue by using chi-square test at 95 % confidence level and margin of error (?) of 0.05. it is re-vealed that there is a relationship between independent and dependent variables with a p-value of 0.009. The conclusion of this study is ergonomic status of working position correlates with the fatigue of workers of CV Sinar Albasia Utama.The owner of the industry is advised to reset the hight of the work-bases and to provide labor-chairs to make the workers can rest in their al-ways standing working position. For the workers, the advice is they have to get used to do mus-cle stretching during work activity or break-time and they have to effectively use the rest periods given.